Dengue and leptospirosis infection during the coronavirus 2019 outbreak in Sri Lanka - Niriella, M.A.; Ediriweera, D.S.; de Silva, A.P.; Premaratna, B.A.H.R.; Jayasinghe, S.; de Silva, H.J. (Oxford University Press, 2021)
ABSTRACT: A significant decrease in dengue fever cases and a contrasting increase in leptospirosis cases were reported for the second quarter of 2020 compared with 2019 in Sri Lanka. In the absence of significant environmental and weather-related differences to account for these changes in incidence, we investigated the possibility that the effects of the COVID-19 pandemic on public health, social behaviour and the restrictions imposed during the lockdown influenced the fluctuations in dengue and leptospirosis infections. KEYWORDS: COVID-19; dengue fever; leptospirosis; pandemic; tropical infections.
Indexed in MEDLINE
Keywords: dengue